Social Foundation and Sociological Substantiation of Positive Legal Responsibility - LIPINSKY, Dmitry A.; IVANOVA, Tatiana N. (Journal of Advanced Research in Law and Economics; Vol 8 No 3 (2017): JARLE Volume VIII Issue 3(25) Summer 2017, 2017)
The authors study the social foundation of positive legal responsibility, analyze social responsibility, which is a basic abstraction for formation of the notion of legal responsibility, and lead a discussion with philosophers and sociologists, who, while studying social responsibility, do not take into account significant characteristics of legal responsibility. The features of legal responsibility are determined on the basis of common characteristics of social responsibility; it is shown how the main qualities and features of social responsibility are reflected in the characteristics of legal responsibility. According to the authors, positive legal responsibility possesses a legal nature, and substantiation of its legal character is predetermined by the necessity for development of a legal state. The study contains definitions of social and legal responsibilities. The authors provide the results of survey of ordinary people and experts on the problems of positive legal responsibility. The authors substantiate the presence of statutory (single) legal responsibility, which is a precondition for realization of positive and negative legal responsibilities. It is concluded that statutory responsibility is predetermined by the law, is set by it, and is protected by state. Statutory responsibility leads to both forms of its realization – positive and negative (voluntary and mandatory). It is proved that both forms do not exclude each other, but can exist within the same legal phenomenon, which is caused by the philosophical law of integrity and struggle of contradictions. The authors determine the common and different features of various forms of realization of legal responsibility and study the possibility of transition of one form of realization of legal responsibility into another. It is concluded that exclusion of responsibility which includes various forms of realization means disappearance of evaluation of legal behavior as responsible or irresponsible.